2006
DOI: 10.1007/s10722-004-0578-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among Brazilian Cultivars and Landraces of Tomato Lycopersicon Esculentum Mill. Revealed by RAPD Markers

Abstract: Random amplified polymorphic DNA markers (RAPD) were used to estimate the variability of 35 tomato accessions (Lycopersicon esculentum Mill.). A total of 257 reproducibly scorable bands were obtained from 20 primers, 78.6% of which were polymorphic. The percentage distribution of RAPD markers shows a bimodal distribution, and the frequency of rare alleles is similar in commercial and landrace accessions. Genetic distances among accessions were calculated and a dendrogram showing the genetic relationships among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 13 publications
2
29
1
2
Order By: Relevance
“…Mesmo as variedades tradicionalmente brasileiras são originadas de sementes trazidas por imigrantes europeus, embora alguns materiais selvagens sejam encontrados eventualmente (CARELLI et al, 2006). Segundo Ferreira (2004), a preferência do consumidor é determinada por características como tamanho, cor, forma, firmeza da polpa e casca e aparência geral do fruto.…”
Section: Introductionunclassified
“…Mesmo as variedades tradicionalmente brasileiras são originadas de sementes trazidas por imigrantes europeus, embora alguns materiais selvagens sejam encontrados eventualmente (CARELLI et al, 2006). Segundo Ferreira (2004), a preferência do consumidor é determinada por características como tamanho, cor, forma, firmeza da polpa e casca e aparência geral do fruto.…”
Section: Introductionunclassified
“…The lack of polymorphism has also been reported in other self-pollinated crops such as soybean, potato, and ground nut [7,11,20]. Such insufficient variability in DNA polymorphism makes it difficult to construct a genetic map, if using populations derived from across between cultivars [2]. A low level DNA polymorphism in cultivated tomato was also reported using AFLP (amplified fragment length polymorphisms) and SSR (simple sequence repeats) primer pairs [14].…”
Section: Resultsmentioning
confidence: 99%
“…The progression has greatly increased the responsibility and visibility of those charged with long-term conservation and the use of plant genetic resources [2]. It is very important to define identity, purity, and stability of varieties for breeder's rights protection as well as for an effective seed quality control program [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of their great potential as a source of variability, the lack of information about their origin, genealogy, agronomic performance and genetic background has hindered the use of these varieties in breeding programs (Carelli et al 2006), causing a narrowing of the genetic base of the new cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies aiming at estimating the diversity of several plant species have been reported for several cultures (Carvalho and Quesenberry 2009, Serqueira-Silva et al 2009, Mazzucato et al 2008, Nick et al 2008, Nizio et al 2008, Rocha et al 2008, Carelli et al 2006, Karasawa et al 2005, Silva et al 2001.…”
Section: Introductionmentioning
confidence: 99%